One-Sample Face Recognition Using HMM Model of Fiducial Areas - Adeniran, J.O.; Ojo, John; Adeniran, Solomon; Adedapo (International Journal of Image Processing (IJIP), 2023)
Ojo, J.A. & Adeniran, S.A. International Journal of Image Processing (IJIP), Volume (5) : Issue (1)